Practice in Vietnam About the Recognition and Enforcement of Foreign Arbitral Awards Under the Code of Civil Procedure 2015 and Recommendations for Improving the Efficiency of Law Application - Tuan, Banh Quoc (VNU Journal of Science: Legal Studies; Vol 35 No 3, 2019)
On the basis of studying the process of applying the provisions of the Civil Procedure Code on the recognition and enforcement of foreign arbitral awards, the author has made comments on regulations of the law as well as analyzed the problems arising from the application of the law in practice as the basis for the proposal of some recommendations to improve the law.